Current Status and Prospects of Anesthesia and Breast Cancer: Does Anesthetic Technique Affect Recurrence and Survival Rates in Breast Cancer Surgery? - Kim, Ryungsa; Kawai, Ami; Wakisaka, Megumi; Kin, Takanori (Frontiers in Oncology, 2022)
The relationship between the anesthetic technique and cancer recurrence has not yet been clarified in cancer surgery. Surgical stress and inhalation anesthesia suppress cell-mediated immunity (CMI), whereas intravenous (IV) anesthesia with propofol and regional anesthesia (RA) are known to be protective for CMI. Surgical stress, general anesthesia (GA) with inhalation anesthesia and opioids contribute to perioperative immunosuppression and may increase cancer recurrence and decrease survival. Surgical stress and GA activate the hypothalamic-pituitary-adrenal axis and release neuroendocrine mediators such as cortisol, catecholamines, and prostaglandin E2, which may reduce host defense immunity and promote distant metastasis. On the other hand, IV anesthesia with propofol and RA with paravertebral block or epidural anesthesia can weaken surgical stress and GA-induced immunosuppression and protect the host defense immunity. IV anesthesia with propofol and RA or in combination with GA may reduce cancer recurrence and improve patient survival compared to GA alone. We review the current status of the relationship between anesthesia and breast cancer recurrence using retrospective and prospective studies conducted with animal models and clinical samples, and discuss the future prospects for reducing breast cancer recurrence and improving survival rates in breast cancer surgery.